Polydopamine-assisted versatile modification of a nucleic acid probe for intracellular microRNA imaging and enhanced photothermal therapy. Issue 13 (12th February 2018) - Zheng, Aixian; Zhang, Xiaolong; Huang, Yanbing; Cai, Zhixiong; Liu, Xiaolong; Liu, Jingfeng
Abstract : Polydopamine can assist the versatile modification of a nucleic acid probe for intracellular miRNA responsed fluorescence imaging and enhanced photothermal therapy. Abstract : MicroRNAs play an important role in various biological processes, and their aberrant expression is closely associated with various human diseases, especially cancer. Real-time monitoring of microRNAs in living cells may help us to understand their role in cellular processes, which can further provide a basis for diagnosis and treatment. In this study, polydopamine was used to assist the versatile modification of a nucleic acid probe for intracellular microRNA imaging and enhanced photothermal therapy. Polydopamine can be covalently linked with a thiol-terminated nucleic acid probe through the Michael addition reaction under slightly alkaline conditions. This modification is mild and can be performed directly in an aqueous solution, which can better resist hydrolysis than the traditional modification processes, resulting in a nanoprobe with better stability and higher loading of nucleic acids. This prepared nanoprobe can easily enter cells without transfection agents and then realize the imaging of intracellular miRNA through fluorescence restoration. Moreover, the coating of PDA can enhance the photothermal conversion efficiency of the nanoprobe, making it suitable for photothermal therapy of cancer. It is expected that the PDA-based versatile modification can help to construct a promising platform for tumor imaging and treatment.